Hubungan Antara Riwayat Pemberian ASI Eksklusif dengan Perkembangan Anak Usia 6-36 Bulan di Wilayah Kerja Puskesmas Buduran: The Relationship Between the History of Exclusive Breastfeeding and the Development of Children Aged 6-36 Months in the Working Area of the Buduran Health Center - Renanda Ayu; Ani Media Harumi; Ahdatul Islamiah; Astuti Setiyani (Gema Bidan Indonesia, 2023)
Exclusive breastfeeding is an important factor for child development which includes gross movements, fine movements, socialization of speech and language independence. The achievement of breastfeeding in Sidoarjo Regency is far below the target, only 2 Puskesmas namely Wonoayu and Sedati have to achieve the target. The purpose of the study was to determine the relationship between a history of exclusive breastfeeding and the development of children aged 6-36 months in the working area of ​​the Buduran Health Center. This research is an analytic study with a cross sectional approach. Samples were taken with a total sampling technique of 40 respondents. The independent variable is exclusive breastfeeding, the dependent variable is the development of children aged 6-36 months. Collecting data using questionnaires and KPSP (Pre-screening Development Questionnaire) sheets. To analyze this relationship, the Chi-Squere test was used with a significance level of 0.05. The results showed that almost all children aged 6-36 months, 95% of children were exclusively breastfed. Then, almost all of the development of children aged 6-36 months, 97.5% of children in Wadung Asih Village, the working area of ​​the Buduran Health Center, are included in the Appropriate Development Category (S). Then the results of the analysis obtained a P Value of 0.000 so it can be concluded that there is a significant relationship between a history of exclusive breastfeeding and the development of children aged 6-36 months in Wadung Asih Village, the working area of ​​the Buduran Health Center.